Pengaruh Promosi Penjualan dan Fasilitas terhadap Keputusan Pembelian Konsumen Tepi Bambu Cafe & Resto Kota Depok - Muchammad Danis Wahyudi; Eigis Yani Pramularso; Hardani Hardani (MAMEN: Jurnal Manajemen, 2025)
The purpose of this study is to evaluate the impact of promotions and facilities offered by Tepi Bambu Café & Resto in Depok on customer purchasing choices. This study uses a quantitative method and conducted a survey of 100 participants who have made purchases at the cafe. The collected data were processed using SPSS version 25 by conducting multiple linear regression analysis. Several studies were conducted, including data quality checks, traditional hypothesis tests, specific hypothesis tests, and assessment of the coefficient of determination. The results showed that the sales promotions offered had a significant impact on purchasing decisions, the facilities offered had a significant impact on purchasing decisions, sales promotions and facilities offered had a significant impact on purchasing decisions simultaneously. With an R² of 0.696, it was found that sales promotion facilities influenced 69.6% of purchasing decisions, while the remaining 30.4% was determined by other factors not considered in this study.